OCCUPATIONAL STRESS A STUDY AMONG FEMALE EMPLOYEES IN KERALA - Miss Sani S and Manoharan Nair (REVIEW OF SOCIAL SCIENCES, 2013)
Stress is an inevitable part of today‘s modern life style. In this fast changing world of today, no individual is free from stress and no profession is free from stress. The nature of work has gone through drastic changes over the last century and it is still changing at whirl wind speed. Stress is a part of everybody’s life. Stress can cause poor work performance and lower employee morale. This paper focuses on the work related stress faced by female employees in selected sectors and their effects. The occupation that I consider more stressful for women’s are police, medical, labors, professors, IT professions. The aim of this study is to identify the factors affecting stress in women employees in different sectors and to see how far the job stress affect work life